2014
DOI: 10.1063/1.4870950
|View full text |Cite
|
Sign up to set email alerts
|

Dual-polarity GaN micropillars grown by metalorganic vapour phase epitaxy: Cross-correlation between structural and optical properties

Abstract: Self-assembled catalyst-free GaN micropillars grown on (0001) sapphire substrates by metal organic vapor phase epitaxy are investigated. Transmission electron microscopy, as well as KOH etching, shows the systematic presence of two domains of opposite polarity within each single micropillar. The analysis of the initial growth stages indicates that such double polarity originates at the micropillar/substrate interface, i.e., during the micropillar nucleation, and it propagates along the micropillar. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 62 publications
5
41
0
Order By: Relevance
“…Regarding the optical properties, Kirste et al observed a high photoluminescence (PL) intensity at the boundaries between N and III‐polar GaN film due to the localized surface potential difference . Coulon et al, on the other hand, demonstrated higher near‐band‐edge luminescence in N‐polar regions of randomly distributed GaN micropillars due to unequal impurity incorporations in different domains . These results indicate that polarity manipulation can be important for formation of desirable film properties amid enhanced luminescence intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the optical properties, Kirste et al observed a high photoluminescence (PL) intensity at the boundaries between N and III‐polar GaN film due to the localized surface potential difference . Coulon et al, on the other hand, demonstrated higher near‐band‐edge luminescence in N‐polar regions of randomly distributed GaN micropillars due to unequal impurity incorporations in different domains . These results indicate that polarity manipulation can be important for formation of desirable film properties amid enhanced luminescence intensity.…”
Section: Introductionmentioning
confidence: 99%
“…However, a comparison with catalyst‐free NWs shows that while the metal catalyst dictates the GaN NW growth and enables thereby a certain size control, it can strongly affect their structural and optical properties . On the other hand, self‐assembled catalyst‐free NWs show a quite broad statistical distribution of the NW size and density []. In this context, catalyst‐free SAG of NWs appears as the most adapted approach to elaborate homogenous GaN NW array.…”
Section: Introductionmentioning
confidence: 99%
“…In the following, we discuss recent reports illustrating such correlation studies of single nitride nanorod heterostructures. More recently the dual polarity has been evidenced in GaN micropillars grown by MOVPE at $1000 C in a study combining KOH etching, TEM-Convergent Beam Electron Diffraction (CBED) and cathodoluminescence (CL) measurements at room temperature (Coulon et al, 2014). Previous structural characterization of GaN layers grown by MOCVD on sapphire substrates showed that their polarity can be controlled by annealing at $1000 C the GaN buffer layer grown at lower temperature ($600 C), with the Ga polarity favored by short annealing times (<20 min) while both Ga and N polarities would coexist for longer annealing times (Sumiya et al, 1999).…”
Section: Nanocharacterization: Structure and Opticsmentioning
confidence: 99%